Positive blood culture and neonatal sepsis – A five-year study - Ferreira, Adriana (2022)
Introduction: Neonatal sepsis remains a major cause of morbidity and mortality in pediatric age. Since the predominant causative microorganisms vary between regions and over time, it is crucial to know the local epidemiology. The aim of this study was to characterize patients with positive blood culture and clinical presentation of sepsis admitted to a Neonatology Unit and identify possible risk factors and implicated microorganisms and respective antimicrobial susceptibility patterns. Methods: This was a retrospective descriptive study of clinical data of patients admitted to the Neonatology Unit of a level II hospital with positive blood culture and clinical presentation of sepsis over five years (2014-2018). Results: Seventy-three culture-proven sepsis cases were identified, 51 (69.9%) of which corresponded to low-birth-weight neonates and 52 (71.2%) to preterm newborns. Most cases (60; 82.2%) concerned late-onset sepsis. The most frequent microorganisms identified were coagulase-negative Staphylococcus (55; 75.3%), mainly associated with late-onset sepsis. Group B Streptococcus and Escherichia coli were the most common microorganisms isolated in early-onset sepsis. No cases of methicillin-resistant Staphylococcus aureus were identified. Coagulase-negative Staphylococcus presented high resistance rates to beta-lactam antibiotics. Conclusions: The results retrieved from this study document the local epidemiology of neonatal sepsis and show a high frequency of late-onset sepsis associated with nosocomial pathogens. Coagulase-negative Staphylococcus spp. are resistant to the most commonly used antibiotics, with these cases requiring the use of vancomycin. It is crucial to implement effective guidelines to control and prevent nosocomial infections and reduce the incidence, morbidity, and mortality of neonatal sepsis, as well as the need for broad-spectrum antibiotics.